Optimalisasi Produktivitas Crawler Crane pada Pekerjaan Pengangkatan Precast Beton Tiang Pancang 35 x 35 cm PT. Wijaya Karya Beton Tbk. - Nayla Hanna Ariza; Wulandari Wulandari; Sandi Prayoga; Abdillah Mursyid; Deny Ernawan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to optimize the productivity of Crawler Crane heavy equipment in lifting precast concrete structural elements at PT Wijaya Karya Beton Tbk. The method used is a descriptive qualitative approach with data collection through direct observation in the field. The data is based on the equipment's operating cycle time and work efficiency. The results of the study show that the Crawler Crane heavy equipment used by PT Wijaya Karya Beton Tbk. produces a productivity of 20 tons/hour or 160 tons/day for 8 hours with the need for 2 units of crawler crane heavy equipment, resulting in a work efficiency of 80%. So the productivity results from the calculation have been optimal, so it is hoped that the results of this study can be a reference in the management of heavy equipment, especially Crawler Cranes in construction work at the Company PT. Wijaya Karya Beton Tbk.